The Social Influence of Da’wah on the Consumptive and Productive Behavior of Muslim Students in North Maluku - Abdurrahman Hi. Usman; Nurmala Sinen; Santi Evari; Nurafni Baharuddin; Nurfahni Abdullah; Nurana Ibrahim Sartoso (Electronic Journal of Education, Social Economics and Technology, 2025)
Student consumptive behavior has become an increasingly complex social phenomenon in the digital era, while social da'wah activities have developed as an important part of Muslim students' social interactions. This study aims to analyze the influence of social da'wah on consumptive and productive behavior of Muslim students in North Maluku. The research employed a quantitative approach with a correlational survey method involving 350 active Muslim students at Khairun University Ternate selected through purposive sampling. Data were collected using a 1-5 Likert scale questionnaire that had been tested for validity and reliability (Cronbach's Alpha ≥0.7), then analyzed using Pearson correlation and multiple linear regression. The results showed that social da'wah had a significant negative effect on consumptive behavior (r = -0.421; p 0.01; R² = 0.176) and a significant positive effect on productive behavior (r = 0.538; p 0.01; R² = 0.289). The influence of social da'wah on productive behavior (28.9%) was greater than on consumptive behavior (17.6%). Dimentional analysis showed that involvement in da'wah communities had the strongest impact compared to campus da'wah activities and social media. There was a dose-response effect where the intensity of involvement was directly proportional to the impact on behavior. This study confirms that social da'wah plays a strategic role in shaping students' character to be wise in consumption and productive in work, and provides an empirical basis for developing more effective campus da'wah programs.